Evaluasi Kinerja Lalu Lintas di Ruas Jalan Jendral Ahmad Yani Depan Gateway Cicadas Kota Bandung - Farhatun, Defi; Hariani, Mira Lestira (Teknik Sipil, Politeknik Negeri Ketapangg, 2024)
One common traffic issue in Bandung City is the congestion on Jalan Jendral Ahmad Yani Cicadas. One of the primary thoroughfares that links different parts of Bandung City is Jalan Jendral Ahmad Yani Cicadas. When this stretch of road gets congested, it causes widespread problems, such as delays in traffic, higher levels of air pollution, and financial losses. This study's overarching goal is to identify the most effective means of reducing traffic congestion and improving overall traffic performance in the region. In order to get to the main data, we assess the geometric conditions of the roads and gather data on traffic. Population statistics for Bandung City 2023 are an example of secondary data. This study's data analysis is predicated on the PKJI 2023 and MKJI 1997 standards. Data processing in Microsoft Excel to determine vehicle volume, speed, capacity, side resistance, degree of saturation, and service level. According to the findings of the evaluation, the biggest bottleneck on Jalan Jendral Ahmad Yani Cicadas in Bandung City happens between 16.00 and 18.00 WIB in the afternoon, with an average level of service (Level of Service) of C following a 30% diversion of traffic volume.